Weather risk management in agriculture using weather derivatives - Martina Bobrikova (Italian Review of Agricultural Economics (REA), 2022)
The purpose of this paper is to examine weather risk management by application of weather derivatives in agriculture and evaluate the hedging efficiency. Agriculture is a sector highly sensitive to meteorological elements that affect the yield of many crops. The underlying weather indices depending on temperature, rainfall and wind speed are analysed. Pricing follows the index modelling method using the Burn analysis valuation for fair premium calculation. The proposal of hedging strategies against excess rainfall in the crop cycle using weather options for Kosice region in the east of Slovakia is investigated and discussed. Results show that the weather derivatives application in weather risk management reduced the yield volatility in agriculture.
Keywords: G13; 330; Weather Risk Management; weather option; rainfall index; burn analysis; hedging efficiency